ANALYSIS OF BANK HEALTH AND MACROECONOMIC STRESS TESTING ON CREDIT RISK - Pandolo, Krisnaldi Prawira; Pahlevi, Cepi; Toaha, Muhammad (Scientium Management Review, 2022)
Bank is a business that has important role for people. But, in recent years there have been problems that have hit banks, namely the Covid-19 pandemic. Banks are required to keep anticipating risks arising from the pandemic. This study aims to analyze the bank health using the RGEC method and do stress testing on credit risk. The research was conducted at BUMN Bank, such as BRI, BNI, BTN and Mandiri in the 2017-2021 period. The research of the bank health used ratio analysis, such as Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM). ), Return On Assets (ROA) and Capital Adequacy Ratio (CAR). In the ratios of NPL, NIM, and CAR it is known that the bank health of all BUMN Bank is at a very healthy level (PK-1). For the ROA ratio, there are several banks that are at PK-4 and PK-5 level, especially in 2019-2021. For the LDR ratio during 2017-2021 there are no BUMN Bank that in the very healthy category. For the stress test measurement using the inflation shock scenario, it can be concluded that when Indonesia's inflation based on the scenario of the Minister of Finance in 2020 was at the level of 5.1%, the Bank's NPL remained in a very healthy category.